Analisis Kandungan Formalin dan Boraks dalam Mi Kuning, Kerupuk Merah, dan Ayam Menggunakan Metode Rapid Test Kit dan Spektrofotometri UV-Vis - Syafriani, Yolanda Febrica; Anis, Mhd.; Kartika, Irma Ratna; Kurniadewi, Fera (Jurnal Kimia Unand, 2024)
Food is one of human’s primary needs to survive and carry out their activities. Food must be safe, nutritious, and high quality when it’s consumed. In order to maintain food quality, some food ingredients, such as yellow noodles, crackers, and chicken, are often added with formaldehyde and borax, which are dangerous ingredients that are prohibited use as Food Additives (BTP) because their health hazards in accordance with Regulation of Minister Health No. 033 of 2012 and Regulation of BPOM No. 22 of 2023. Therefore, this research aims to identify qualitatively and determine the formaldehyde and borax levels quantitatively in yellow noodles, red crackers, and chicken as an effort to ensure the food safety. The method used in qualitative analysis is a rapid test kit and quantitative is UV-Vis spectrophotometry at a wavelength of 412 nm for formaldehyde and 551 nm for borax. The results of the qualitative analysis test showed that the yellow noodle sample contained formaldehyde and borax as indicated by the color change of the test stick to purple and red, respectively. Meanwhile, according to quantitative analysis, yellow noodles also contained formaldehyde and borax with average levels of 479.09 mg/kg and 44.43 mg/kg, respectively. Red crackers and chicken samples are free from formaldehyde and borax content.